The Administration Model of the Child Development Center for Enhancing the Student’s Innovator - Boonchit, Yanisa (Rajapark Journal, 2022)
The objectives of this study were: 1) to study the state and guidelines for the administration of child development centers; 2) to develop the administration model of child development centers; and 3) to evaluate the administration model of child development centers for enhancing the students’ innovator. This study was a research and development study. The sample groups for data collection regarding the state of the administration consisted of personnel in the division or department of education, heads, and teachers; a total of 315 informants were involved in this study. The model was examined at five child development centers. And data were collected by connoisseurship from nine experts, selected by purposive sampling. The research instruments consisted of a questionnaire, an interview form, an observation form, and an evaluation form. Data were analyzed using inferential statistical tools, including the mean, standard deviation, and content analysis. The research findings were as follows: 1) The state of the administration of the child’s development showed that the administration in overall terms and in each aspect was at a high level. 2) The model consisted of principles of administration, processes of administration, products, and terms of use. 3) The examination of the model revealed that all five centers could operate in accordance with the guidelines of the model, and 85.51 percent of students in the centers that tested the model expressed the characteristics of innovators in three aspects at levels 2 and 3. The overall satisfaction with the model was high. Moreover, the certification of the model by connoisseurship showed that the model was accurate, appropriate, feasible, and useful.